Electrode Materials, Electrolytes, and Challenges in Nonaqueous Lithium‐Ion Capacitors. Issue 17 (12th March 2018) - Li, Bing; Zheng, Junsheng; Zhang, Hongyou; Jin, Liming; Yang, Daijun; Lv, Hong; Shen, Chao; Shellikeri, Annadanesh; Zheng, Yiran; Gong, Ruiqi; Zheng, Jim P.; Zhang, Cunman
Abstract: Among the various energy‐storage systems, lithium‐ion capacitors (LICs) are receiving intensive attention due to their high energy density, high power density, long lifetime, and good stability. As a hybrid of lithium‐ion batteries and supercapacitors, LICs are composed of a battery‐type electrode and a capacitor‐type electrode and can potentially combine the advantages of the high energy density of batteries and the large power density of capacitors. Here, the working principle of LICs is discussed, and the recent advances in LIC electrode materials, particularly activated carbon and lithium titanate, as well as in electrolyte development are reviewed. The charge‐storage mechanisms for intercalative pseudocapacitive behavior, battery behavior, and conventional pseudocapacitive behavior are classified and compared. Finally, the prospects and challenges associated with LICs are discussed. The overall aim is to provide deep insights into the LIC field for continuing research and development of second‐generation energy‐storage technologies. Abstract : The working principle of lithium‐ion capacitors (LICs) is discussed. The recent advances of LIC electrode materials and electrolyte materials, particularly activated carbon and lithium titanate, are reviewed. The charge‐storage mechanisms for intercalative pseudocapacitive behavior, battery behavior, and conventional pseudocapacitive behavior are classified and compared. Finally, the prospects and challenges associated with LICs are also discussed.